Optimization of Neutron Collimator in The Thermal Column of Kartini Research Reactor for in vitro and in vivo Trials Facility of Boron Neutron Capture Therapy using MCNP-X Simulator - Ranti Warfi; Andang Widi Harto; Yohannes Sardjono; Widarto Widarto (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
The optimization of thermal column collimator has been studied which resulted epithermal neutron beam for in vivo and in vitro trials of Boron Neutron Capture Therapy (BNCT) at Kartini Research Reactor of 100 kW by means of Monte Carlo N-Particle Extended (MCNP-X) codes. The design criteria were based on recommendation from the International Atomic Energy Agency (IAEA). MCNP-X calculations indicated by using 5 cm thickness of Ni as collimator wall, 30 cm thickness of Al as moderator, 20 cm thickness of 60Ni as filter, 2 cm thickness of Bi as γ-ray shielding, 3 cm thickness of 6Li2CO3-polyethylene as beam delimiter, and for in vivo in vitro trials purpose, aperture was designed 8 cm radius size, an epitermal neutron beam with an intensity 1.13E+09 n.cm-2.s-1, fast neutron and γ-doses per epithermal neutron of 1.76E-13 Gy.cm2.n-1 and 1.45E-13Gy.cm2.n-1,minimum thermal neutron per epithermal neutron ratio of 0.008,and maximum directionality of 0.73, respectively could be produced. The results have passed all the IAEA’s criteria.